Scope Management Analysis of Construction Work for Mix-Used Building Projects in the City of Jakarta - Nanang Hidayat; Manlian R. A. Simanjuntak (International Journal Labs, 2023)
Planning the process of activities and work items in detail on the project is very important in construction work because it can affect the process of implementing project activities which starts from the bidding stage of a project. In this case, the construction service provider involved in a project is required to understand how the contents and conditions have been included in a construction project work contract so that they can identify the total number of construction work activities according to the scope of work. In this stud,y the method of analysis was used by taking references from several previous studies related to the management of the scope of construction work. Apart from the literature, data collection and interviews were also carried out with service providers, namely the main contractor for the ABC building construction project in the city of Jakarta. By using knowledge and experience for the implementation of project management, in terms of how the contractor can carry out the process of preparing the scope of construction work in detail. Therefore, information on the results of processed data from respondents who were directly involved in the implementation process of the ABC Building project was also obtained regarding the factors and variables that influence the drafting process to control the scope of construction work to help improve project completion performance. In this case, it produces data that it is known that there are 6 variables that have a strong influence on the preparation of the scope of construction work for the ABC Building project.